Assessment of effect of health song on oral hygiene status among visually impaired children - J John Smith; Jithesh Jain; S R Ananda; Bhakti Jadduram Sadhu (Wolters Kluwer Medknow Publications, 2022)
Background: The visually impaired depend much on sound, speech, and touch, and therefore, promotion of oral hygiene maintenance through a health song can improve their oral hygiene practices. Aim and Objectives: To assess the effectiveness of oral health song on oral hygiene status among visually impaired children at baseline and after oral health education (OHE) at different time intervals. Materials and Methods: A study was carried out in Government Blind School, Salem, with prior permission. Out of 63 students, 57 students were taken to the study based on the inclusion and exclusion criteria. Seven students were lost to follow-up during the second visit and 9 students during the last visit. During the first visit, a health talk about brushing techniques was given without using any audiovisual aids, and oral health song which is of 2 min duration was taught to the students. Each of the students was given a tooth cast model and was taught how to brush. The oral hygiene status was assessed at baseline and 15th and 45th day using visible plaque index (VPI) and gingival bleeding index (GBI). Statistical analysis was done using IBM SPSS Statistics 25. The Bonferroni test was to compare the VPI and GBI scores between the baseline, 15 days, and 45 days, and P < 0.05 was considered statistically significant. Results: VPI and GBI scores were found to be statistically significant at different intervals (P < 0.001). The VPI anterior and posterior percentage (P < 0.001) and GBI anterior and posterior percentage (P < 0.001) at different intervals were found to be statistically highly significant. Conclusion: A song with music can increase interest and helps them retain information easily, which was found to be effective in the present study.